The X-ray evolution and geometry of the 2018 outburst of XTE J1810−197. Issue 4 (30th April 2021) - Borghese, A; Rea, N; Turolla, R; Rigoselli, M; Alford, J A J; Gotthelf, E V; Burgay, M; Possenti, A; Zane, S; Coti Zelati, F; Perna, R; Esposito, P; et al.
ABSTRACT: After 15 yr, in late 2018, the magnetar XTE J1810−197 underwent a second recorded X-ray outburst event and reactivated as a radio pulsar. We initiated an X-ray monitoring campaign to follow the timing and spectral evolution of the magnetar as its flux decays using Swift, XMM–Newton, NuSTAR, and NICER observations. During the year-long campaign, the magnetar reproduced similar behaviour to that found for the first outburst, with a factor of 2 change in its spin-down rate from ∼7.2 × 10 −12 to ∼1.5 × 10 −11 s s −1 after two months. Unique to this outburst, we confirm the peculiar energy-dependent phase shift of the pulse profile. Following the initial outburst, the spectrum of XTE J1810−197 is well modelled by multiple blackbody components corresponding to a pair of non-concentric, hot thermal caps surrounded by a cooler one, superposed to the colder star surface. We model the energy-dependent pulse profile to constrain the viewing and surface emission geometry and find that the overall geometry of XTE J1810−197 has likely evolved relative to that found for the 2003 event.